Efektivitas Program Pendampingan Usaha Mikro di Dinas Koperasi Usaha Mikro Kecil dan Menengah Kota Bandung - Muhammad Fachri Fermana Nurhidayat; Hari Bustomi Arifin (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to determine the effectiveness of the Micro Business Actor Assistance program at the Bandung City KUMKM Office. Micro business actor assistance is a program of the Bandung city government through the Bandung City KUMKM Office where the micro business actor assistance program is a program to improve micro business actors so that they can be competitive and improve the quality of micro business actors. However, in its implementation, the Micro Business Actor Assistance at the Bandung City KUMKM Office has not been optimal and there are several obstacles such as the characteristics of the indifferent community and technical support still needs to be overcome to optimize the results of the program. Overall, Micro Business Actor Assistance is considered effective in achieving the goals of empowering micro business actors and improving quality and competitiveness at the Bandung City KUMKM Office. From the results of the study, it is known that 4 Themes, 9 Categories, and 108 Codes were found, the method used in this study is a qualitative method with a case study. In this study, data collection techniques were carried out by interviews, observation, documentation, and literature studies. The informants in this study include: Plta Kasie, head of the micro business sector, and assistants to micro business actors in the Kiaracondong, Batununggal and Lengkong sub-districts. The data analysis used in this study is the Miles & Huberman interactive model data analysis which consists of several components, namely data collection, data reduction, data presentation and conclusions or verification. Data analysis was carried out using the Atlas.ti software tool.